Diversion-p64: results from an international, prospective, multicenter, single-arm post-market study to assess the safety and effectiveness of the p64 flow modulation device. (15th November 2021) - Bonafe, Alain; Perez, Marta Aguilar; Henkes, Hans; Lylyk, Pedro; Bleise, Carlos; Gascou, Gregory; Sirakov, Stanimir; Sirakov, Alexander; Stockx, Luc; Turjman, Francis; Petrov, Andrey; Roth, Christian; et al.
Abstract : Background: The use of flow diversion to treat intracranial aneurysms has increased in recent years. Objective: To assess the safety and angiographic efficacy of the p64 flow modulation device. Methods: Diversion-p64 is an international, prospective, multicenter, single-arm, study conducted at 26 centers. The p64 flow modulation device was used to treat anterior circulation aneurysms between December 2015 and January 2019. The primary safety endpoint was the incidence of major stroke or neurologic death at 3–6 months, with the primary efficacy endpoint being complete aneurysm occlusion (Raymond-Roy Occlusion Classification 1) on follow-up angiography. Results: A total of 420 patients met the eligibility criteria and underwent treatment with the p64 flow modulation device (mean age 55±12.0 years, 86.2% female). Mean aneurysm dome width was 6.99±5.28 mm and neck width 4.47±2.28 mm. Mean number of devices implanted per patient was 1.06±0.47, with adjunctive coiling performed in 14.0% of the cases. At the second angiographic follow-up (mean 375±73 days), available for 343 patients (81.7%), complete aneurysm occlusion was seen in 287 (83.7%) patients. Safety data were available for 413 patients (98.3%) at the first follow-up (mean 145±43 days) with a composite morbidity/mortality rate of 2.42% (n=10). Conclusions: Diversion-p64 is the largest prospective study using the p64 flow modulation device. The results of this study demonstrate that the device has a high efficacy and carries a low rate of mortality and permanent morbidity.